1977
DOI: 10.3109/00016347709162123
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Bone Mineral Content During Pregnancy and Lactation

Abstract: In order to study changes in the calcium depots of the body during pregnancy and lactation, bone mineral deteminations were performed on fourteen pregnant women and eighteen mothers post partum by X-ray spectrophotomeyry. Pregnant women exhibited a loss in trabecular bone but not in cortical bone when measured once during late first or early second trimester and again one week post partum. Lactating women who nursed less than three months lost mineral during the first three months and than regained it while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(59 citation statements)
references
References 6 publications
4
52
1
1
Order By: Relevance
“…Although there have been some reports on the effects of pregnancy on bone mass (1-6), since the measurement sites and techniques of bone mass measurement were different in each study, it is still con troversial whether bone mass decreases during preg nancy. However, it has been suggested in both the human and the rat studies that the axial bone mass might decrease during pregnancy (2)(3)(4), and that the appendicular bone mass does not decrease (2,5,6). In the present study, the BMD of the axial bone, which was lumbar spine, decreased during pregnancy.…”
Section: Discussioncontrasting
confidence: 55%
“…Although there have been some reports on the effects of pregnancy on bone mass (1-6), since the measurement sites and techniques of bone mass measurement were different in each study, it is still con troversial whether bone mass decreases during preg nancy. However, it has been suggested in both the human and the rat studies that the axial bone mass might decrease during pregnancy (2)(3)(4), and that the appendicular bone mass does not decrease (2,5,6). In the present study, the BMD of the axial bone, which was lumbar spine, decreased during pregnancy.…”
Section: Discussioncontrasting
confidence: 55%
“…Several investigators, including ourselves, have reported that bone mineral density decreases during pregnancy or puerperium [1,[14][15][16][17][18][19]. As we mentioned previously [1], the reason for increased bone turnover during pregnancy despite a hyperestrogenic environment is unclear.…”
Section: Assay For Ctx Ntx and Other Markers In Urinementioning
confidence: 76%
“…This reduction during lactation is seen in most of the reports that have studied this subject. 19,22,24,25 Sowers et al 26 verified a reduction in bone mineral density among women that suckled for more than 6 months, with the return to the basal level of bone mineral density occurring 12 months after childbirth. The reduction in bone mineral density during lactation is explained by the decrease in estrogen levels due to the decrease in follicle-stimulating hormone (FSH), caused by the increase of prolactin.…”
Section: Discussionmentioning
confidence: 99%